2010
DOI: 10.1038/hr.2010.21
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in CYP11B2 and CYP11B1 genes associated with primary hyperaldosteronism

Abstract: Several frequent polymorphisms in the CYP11B2 gene are suggested to be associated with essential hypertension and aldosterone secretion. In this study, we investigated the association of polymorphisms in CYP11B2 and CYP11B1 genes with the risk of primary hyperaldosteronism (PH). Three polymorphisms in the CYP11B2 gene (intron 2 conversion, rs1799998 and rs4539) and two polymorphisms in the CYP11B1 gene (rs6410 and rs6387) were analyzed in patients with PH and in the normal population. The rs6410 allelic freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…New therapeutic options suggested by our study for control of blood pressure include the genes Calcrl , Cyp11b1 and Prcp [36]. CALCRL (calcitonin receptor-like) is a multifunctional vasodilator peptide that was persistently upregulated in aged rats whereas Cyp11b1 is associated with essential hypertension and had decreased levels in both age groups [37]. Activity modulators available for all three of these genes [38][40].…”
Section: Discussionmentioning
confidence: 93%
“…New therapeutic options suggested by our study for control of blood pressure include the genes Calcrl , Cyp11b1 and Prcp [36]. CALCRL (calcitonin receptor-like) is a multifunctional vasodilator peptide that was persistently upregulated in aged rats whereas Cyp11b1 is associated with essential hypertension and had decreased levels in both age groups [37]. Activity modulators available for all three of these genes [38][40].…”
Section: Discussionmentioning
confidence: 93%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Aldosterone production has been reported to associate with variation at this locus [À344C/T, rs1799998]. 1 Moreover, clinically overt phenotypes that may be mediated by aldosterone have been linked to this SNP.…”
mentioning
confidence: 99%
“… 39 It has been reported that there is a significant association between polymorphisms in CYP11B2 and CYP11B1 and a genetic predisposition towards primary hyperaldosteronism. 40 …”
Section: Discussionmentioning
confidence: 99%
“…39 It has been reported that there is a significant association between polymorphisms in CYP11B2 and CYP11B1 and a genetic predisposition towards primary hyperaldosteronism. 40 Several studies have reported that some genetic loci associated with lung-related diseases overlap with loci for pulmonary fibrosis. [41][42][43] For example, two chronic obstructive pulmonary disease-associated loci (FAM13A and DSP) overlap with loci for lung function and pulmonary fibrosis, 42 while five pulmonary fibrosis-associated loci (DPP9, DSP, FAM13A, IVD, and MUC5B) are also significantly associated with interstitial lung abnormalities.…”
Section: Discussionmentioning
confidence: 99%